2020
DOI: 10.3390/foods9111554
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure Estimation to Chemicals Transferred from Milk and Dairy Products Packaging Materials in Spanish Child and Adolescent Population

Abstract: Packaging materials are subject to risk assessment since they can transfer their components to the food, and they may constitute a risk for the consumers’ health. Therefore, estimating the exposure to chemicals migrating from packaging is required. In this study, a novel approach based on a total diet study (TDS)-like investigation to evaluate the exposure to chemicals transferred from the packaging was presented. The proposed methodology involved a non-targeted gas chromatography coupled to mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…While several prior studies have measured concentrations of ortho-phthalates and plasticizers in foods, many are not directly comparable to our study due to differences in the food items sampled or the sources of foods (i.e., grocery store or market). One prior study measured DEHT in 14 milk and dairy supermarket products using analytical methods similar to our study and reported that all DEHT concentrations were below the LOQ of 0.05 µg/g [28]. One potentially relevant study is by Cao et al (2015) where they quantified the concentrations of DiBP, DnBP, DEHP, and DEHA, in pizza, fries, chicken nuggets, and hamburgers as part of the Canadian 2013 Total Diet Study and used analytical methods similar to our study [29].…”
Section: Discussionmentioning
confidence: 90%
“…While several prior studies have measured concentrations of ortho-phthalates and plasticizers in foods, many are not directly comparable to our study due to differences in the food items sampled or the sources of foods (i.e., grocery store or market). One prior study measured DEHT in 14 milk and dairy supermarket products using analytical methods similar to our study and reported that all DEHT concentrations were below the LOQ of 0.05 µg/g [28]. One potentially relevant study is by Cao et al (2015) where they quantified the concentrations of DiBP, DnBP, DEHP, and DEHA, in pizza, fries, chicken nuggets, and hamburgers as part of the Canadian 2013 Total Diet Study and used analytical methods similar to our study [29].…”
Section: Discussionmentioning
confidence: 90%
“…Dibutyl phthalate and bis(2-ethylhexyl) phthalate (DEHP) were also detected. These compounds, as well as plasticizers, can be found in printing ink formulations and also have been employed as solvents to hold color [43]. Triphenyl phosphate is used as a plasticizer for coatings and lacquers, as well as a flame retardant and solvent [44,45], while di(ethylene glycol) dibenzoate is a plasticizer for polyvinyl chloride acetate and a component of adhesives [46].…”
Section: Semi-volatile Compounds By Gc-msmentioning
confidence: 99%
“…Further data and specific regulations that properly set BPA maximum residue limits for different food items and confirm or modify the current t-TDI are required (EFSA, 2015). Milk is widely consumed by adults, infants, children, and toddlers, thus the occurrence of quantifiable levels of contaminants along the milk chain is a matter of public health concern (Chege and Ndungu, 2016;van Asselt et al, 2017;European Council, 2017;Mercogliano and Santonicola 2018;Lestido-Cardama et al, 2020).…”
Section: Bpa Exposure Levels In Milkmentioning
confidence: 99%